North Atlantic Regional Water Resources Study. Appendix R. Water Supply. - CORPS OF ENGINEERS NEW YORK NORTH ATLANTIC DIV (1972)
While the North Atlantic REgion's 41-inch average annual precipitation is more than adequate to meet both present and future water supply needs, there is a definite need for further development and management of water sources to keep abreast of the increasing demands of anticipated population growth and urban and industrial development. The potential plight of the Region's water supply situation was brought into proper, if somewhat startling, perspective during the five-year drought that ended in 1967. Many sectors of the NAR experienced critical water supply shortages, and some 14 million people, about 28% of the REgion's population, were subjected to water-use restrictions. That drought is now history, but it provided a stark reminder that the NAR's water supplies are barely adequate to meet present needs under traditional unlimited or unrestrained use patterns. The urgency of this situation is magnified when we look into the future. The population of the Region, approximately 50 million, is growing and projected to double by 2020. While the population increases, individual use of water is also increasing. The analysis in this Appendix has been divided into two major categories: public water supply, including all water supplied from central systems, both public and private; and industrial water supply, which includes all water used by the manufacturing industries in the Region. Summaries of the rural water supply situation and an up-to-date examination of developing desalting technologies are also included in the Appendix as separate chapters. Appendix R to report dated Jun 72, AD-A036 616. See also Appendix S, AD-A036 639.